Cybercrime - Stefoff, Rebecca, 1951- (Marshall Cavendish Benchmark, 2009)
An introduction to forensic science that focuses on crimes that occur over the Internet, and describes a brief history of computer forensics, phone phreakers, hackers, wire tapping, and other related topics.